Full bridge converter based independent phase control of a permanent magnet reluctance generator for wind power conversion systems - (:unkn) unknown (My University, 2018)
A Permanent Magnet Reluctance Generator (PMRG) possesses important features such as simplicity andlow cost. Absence of rotor winding allows the generator to run in a wide speed range. The PMRG may have potentialto be used in wind power conversion systems. An asymmetric half bridge (AHB) converter may be acceptable as aclassical converter topology for PMRGs and offers independent phase control. The AHB converter with a torque rippleminimization-assisted maximum power point tracking algorithm not only provides significant torque ripple reductionon the mechanical side but also allows conversion of maximum wind energy to electrical energy. The major drawbackis that the AHB converter is not commercially available as a single module; hence, manual construction by combiningdiscrete components is required. Instead, this work introduces for the first time, the use of a full bridge (FB) converterfor independent phase control of the PMRG. The main advantage is that the FB converter is commercially availableas a standard intelligent power module. In order to obtain unidirectional current as in the AHB converter, modifieddelta configuration of the phase windings has been used. The experimental results under fixed and variable wind speedconditions confirm the effectiveness of the proposed control-converter configuration.
Keywords: Bilgisayar Bilimleri, Yapay Zeka; Bilgisayar Bilimleri, Sibernitik; Bilgisayar Bilimleri, Donanım ve Mimari; Bilgisayar Bilimleri, Bilgi Sistemleri; Bilgisayar Bilimleri, Yazılım Mühendisliği; Bilgisayar Bilimleri, Teori ve Metotlar; Mühendislik, Elektrik ve Elektronik